Testing and modelling of a 2.5 MW wind turbine gearbox: Influence of lubricant formulation - Carlos M C G Fernandes (2023)
This study aimed to evaluate the efficiency of different ISO VG 320 oil formulations used in a 2.5 MW wind turbine gearbox. Two commercially available lubricants, a mineral oil and a polyalphaolefin (PAO) lubricant, were tested under realistic operating conditions using a customized test rig.Measurements showed that the overall efficiency of the mineral lubricant was higher than that of the PAO lubricant, but the difference was only 0.1% in degree of efficiency. Detailed oil analysis revealed that the mineral lubricant generated more wear particles.A power loss model was also implemented to predict the efficiency of the gearbox, and the results of the model were found to be in agreement with the experimental results. The study concluded that the mineral oil presented higher efficiency than the PAO oil due to its lower viscosity within the narrow operating temperature range imposed on the gearbox. Nevertheless, it is important to note that the observed differences in efficiency may be attributed, in part, to measurement uncertainties and the fact that the mineral lubricant has 10% lower viscosity at the operating temperature compared to the PAO lubricant. Ziel dieser Studie war es, die Effizienz verschiedener ISO VG 320-olformulierungen zu bewerten, die in einem 2,5-MW-Windturbinengetriebe verwendet werden. Zwei handelsubliche Schmierstoffe, ein Mineralol und ein Polyalphaolefin (PAO)-Schmierstoff, wurden unter realistischen Betriebsbedingungen mit einem massgeschneiderten Prufstand getestet.Die Messungen ergaben, dass der Gesamtwirkungsgrad des mineralischen Schmierstoffs hoher war als der des PAO-Schmierstoffs, der Unterschied betrug jedoch nur 0,1 Prozentpunkte im Wirkungsgrad. Eine detaillierte olanalyse ergab, dass der mineralische Schmierstoff mehr Verschleisspartikel erzeugte.Zur Vorhersage des Wirkungsgrads des Getriebes wurde ausserdem ein Verlustleistungsmodell implementiert, dessen Ergebnisse mit den Versuchsergebnissen ubereinstimmten. Die Studie kam zu dem Schluss, dass das Mineralol aufgrund seiner geringeren Viskositat innerhalb des engen Betriebstemperaturbereichs des Getriebes einen hoheren Wirkungsgrad aufweist als das PAO-ol. Es ist jedoch zu beachten, dass die beobachteten Unterschiede im Wirkungsgrad zum Teil auf Messunsicherheiten und die Tatsache zuruckzufuhren sind, dass der mineralische Schmierstoff bei der Betriebstemperatur eine um 10% niedrigere Viskositat als der PAO-Schmierstoff aufweist.